Answer:
a) x = -270
b) y = 304/9 or y = 33.78
c) x = -37.8
Step-by-step explanation:
y varies directly with x so y = kx
a)
y = kx
k = y/x
k = 10/-30 = -1/3
So
y = -1/3 x
If y = 90 then
90 = -1/3 x
x = 90 *(-3) = -270
b)
k = y/x
k = -19/-4.5
k = 38/9
So
y = 38/9 x
If x = - 8 then
y = 38/9 *(-8)
y = 304/9 or y = 33.78
c)
k = y/x
k = -4.3 / 12.9
k = - 1/3
So
y = -1/3 x
If y = 12.6 then
12.6 = -1/3 x
x = 12.6 *(-3)
x = -37.8
Step-by-step explanation:
Given
f(x) = 2x - 1
f^-1 (x) = ?
Now
Let y = f(x)
or y = 2x - 1
Interchanging the role of x and y
x = 2y - 1
x + 1 = 2y
y = <u>x </u><u>+</u><u> </u><u>1</u>
2
Therefore f^-1(x) = <u>x </u><u>+</u><u> </u><u>1</u>
2
Hope it will help you :)
Answer:
The answer is A.
Step-by-step explanation:
Negative integers have this sign "-" before the number. Also, zero is neither positive nor negative.